Internal stress distribution in weld-affected zone under the effect of constrained loads; MATEC Web of Conferences; Vol. 194 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment (HMTTSC 2018) - Hapov N. V. Nikita (Les Ulis, EDP Sciences, 2018)
Title screen